Sifat-sifat penyalaan dan pembakaran briket biomassa, briket batubara dan arang kayu - Siti Jamilatun (Jurnal Rekayasa Proses, 2008)
In general, combustion of solid material consists of several steps including heating, drying, de-volatilization and burning of the charcoal. The factors that determine combustion characteristics of briquettes are the rate of combustion, heating value, density and amount of pollutants or volatile compounds produced. The present work aimed at determining combustion characteristics of various kinds of briquettes from biomass, wood charcoal and coal including the rate of combustion, duration of briquettes burn to ashes, the initial ignition, amount of smoke or volatile compounds produced, heating value and duration for boiling one liter of water. The experimental work was performed by burning 250 grams of each briquette. The results showed that coconut shell had the longest combustion duration (116 minutes) with a combustion rate of 126.6 grams/second. In comparison with other biomass briquettes and wood choarcoal, coconut shell had the highest heating values of 5,779.11 cal/gram which was close to heating value of coal briquette (6,058 cal/gram). All briquettes studied in the present work showed a reasonable duration and needed about 5 – 7 minutes to boil one litter of water.